2015
DOI: 10.3748/wjg.v21.i41.11767
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer: Metastases to a single organ

Abstract: Colorectal cancer (CRC) is a common malignancy worldwide. In CRC patients, metastases are the main cause of cancer-related mortality. In a group of metastatic CRC patients, the metastases are limited to a single site (solitary organ); the liver and lungs are the most commonly involved sites. When metastatic disease is limited to the liver and/or lungs, the resectability of the metastatic lesions will dictate the management approach and the outcome. Less commonly, the site of solitary organ CRC metastasis is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
218
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(223 citation statements)
references
References 139 publications
4
218
0
1
Order By: Relevance
“…Vatandoust et al reported that patients with PM CRC who underwent curative surgery could expect long-term survival (28). Similarly to Vatandoust et al's report, MSI-H-PM also conferred a better prognosis in patients with curatively resected stage IV CRC in our study.…”
Section: Survival Analysis Of Patients With Stage IV Colorectal Cansupporting
confidence: 87%
“…Vatandoust et al reported that patients with PM CRC who underwent curative surgery could expect long-term survival (28). Similarly to Vatandoust et al's report, MSI-H-PM also conferred a better prognosis in patients with curatively resected stage IV CRC in our study.…”
Section: Survival Analysis Of Patients With Stage IV Colorectal Cansupporting
confidence: 87%
“…Cancer invasion and distant metastasis, which are complex, multistep processes that are likely controlled by various genetic and/or epigenetic changes, are the leading causes of more than 90% of cancer-related deaths, including CRC deaths [22]. However, the regulatory factors that are responsible for molecular changes that initiate metastatic progression have not been defined.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is the dominant cause of death in patients with colon cancer [3]. The mechanisms behind colon cancer metastasis remains elusive but accumulating data indicate that increased expression of adhesion molecules and chemokines facilitate colon cancer migration and spread [4].…”
Section: Introductionmentioning
confidence: 99%